Research on Power Efficiency of DC Microgrids Considering Fire Protection Systems - Ju-Ho Park; Sang-Yong Park (Energies)
Due to the development of power semiconductors and the increase in digital loads, DC microgrids are receiving attention, and their application scope is rapidly expanding. As the technological stability of high-voltage direct current (HVDC) continues to rise, the potential of low-voltage direct current (LVDC) distribution systems is becoming increasingly intriguing. Many researchers are actively conducting safety and efficiency research on DC distribution systems and power grids. In LVDC distribution systems, small-scale DC microgrids are formed by renewable energy sources supplying DC power. This paper analyzes the efficiency improvement that can be achieved by integrating a fire protection system into a DC microgrid. This research analyzed the changes when fire protection systems such as receivers, transmitters, fire alarms, emergency lighting, and evacuation guidance, which have traditionally used AC power, were converted to DC circuits. As a result, the power supply infrastructure within the DC microgrid can be simplified, energy loss can be reduced, and the stability of the power system can be improved. The research results of this paper suggest that DC circuit-based fire protection facilities can positively impact future smart grid and renewable energy goals.